Pengaruh Tax Planning, Beban Pajak Tangguhan, Ukuran Perusahaan dan Corporate Social Responsibility Terhadap Manajemen Laba - Fikri Azhari Ramadhani; Tantina Haryati (Journal of Management and Bussines (JOMB), 2023)
The aim of this research is to find the influence of Tax Planning, deferred tax burden, company size, and Corporate Social Responsibility on earnings management in food and beverage sector companies listed on the Indonesia Stock Exchange. This research uses purposive sampling as a sampling approach. The conclusion is that Tax Planning and company size both have an influence on earnings management, but deferred tax burden and Corporate Social Responsibility influence earnings management. Keywords: Deferred Tax Burden, Corporate Social Responsibility, Profit Management, Tax Planning, Company Size